2017
DOI: 10.1016/j.cbpa.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Rates of oxygen uptake increase independently of changes in heart rate in late stages of development and at hatching in the green iguana, Iguana iguana

Abstract: Oxygen consumption (VO), heart rate (f), heart mass (M) and body mass (M) were measured during embryonic incubation and in hatchlings of green iguana (Iguana iguana). Mean f and VO were unvarying in early stage embryos. VO increased exponentially during the later stages of embryonic development, doubling by the end of incubation, while f was constant, resulting in a 2.7-fold increase in oxygen pulse. Compared to late stage embryos, the mean inactive level of VO in hatchlings was 1.7 fold higher, while f was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Popularly known as green iguana, Iguana iguana iguana, is widely distributed in Central and South America, occurring from northern Mexico to south‐eastern Paraguay and Brazil (Barten, ; Blair, ; Campos & Desbiez, ; Swanson, ). Green iguana was established as an experimental species by several biological studies (Butler & Northcutt, ; Foster & Hall, ; Janke, Erpenbeck, Nilson, & Arnason, ; Sartori, Abe, Crossley, & Taylor, ; Sartori, Taylor, Abe, & Crossley, ), although details of its embryonic development had not been widely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Popularly known as green iguana, Iguana iguana iguana, is widely distributed in Central and South America, occurring from northern Mexico to south‐eastern Paraguay and Brazil (Barten, ; Blair, ; Campos & Desbiez, ; Swanson, ). Green iguana was established as an experimental species by several biological studies (Butler & Northcutt, ; Foster & Hall, ; Janke, Erpenbeck, Nilson, & Arnason, ; Sartori, Abe, Crossley, & Taylor, ; Sartori, Taylor, Abe, & Crossley, ), although details of its embryonic development had not been widely explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, the size of the heart relative to the size of the embryo decreased from 0.46% at 50% incubation to 0.31% at 90% incubation (Table 1). This is also the case for the turtles Emys orbicularis (from approximately 0.56% at 50% incubation to 0.31% when close to hatching; Nechaeva et al, 2007) and Lepidochelys olivacea (from 0.46% at 70% incubation to 0.39% at 90%; Crossley et al, 2017a), and for the lizard Iguana iguana (from 0.35% at 30% incubation to 0.26% at 90% incubation; Sartori et al, 2017). This difference in heart growth, when compared with the body mass increase, could be offset to some extent by the reduction in tissue oxygen requirement of the embryo, reflected by the decrease in mass-specific VȮ 2 (Sartori et al, 2017) and a consequent decrease in massspecific O 2 pulse, as described for the marine iguana by Butler and colleagues (2002).…”
Section: Discussionmentioning
confidence: 53%
“…f H of snapping turtle embryos decreased significantly at the end of incubation, a common pattern of members of the order Testudines (Alvine et al, 2013;Birchard and Reiber, 1996;Crossley, 1999;Birchard, 2000;McGlashan et al, 2015;Taylor et al, 2014) and in contrast to the relatively constant f H during incubation of Squamata (Birchard and Reiber, 1996;Nechaeva et al, 2007;Du et al, 2009;Sartori et al, 2017). In snapping turtles, f H reduction has been related to the onset of parasympathetic tone, which is present at 70% incubation (Alvine et al, 2013), in comparison to the late onset of vagal tone found in green iguana (Sartori et al, 2015) and the lack of vagal tone during incubation in the American alligator (Eme et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations